Influence of comorbidities on the health of the elderly in the face of the Covid-19 pandemic: a integrative review (Research, Society and Development, 2021)
Objective: To elucidate, through a integrative review, scientific evidence about the influence of comorbidities on the health of the elderly against the pandemic of COVID-19. Methods: This is a integrative literature review study, conducted in the VHL database through the controlled descriptors elderly, comorbidity and COVID-19, as well as its translations into Spanish and English, according to the DeCS and Mesh, published between the years 2020 and May 2021. Results: A total of 12 comorbidities associated with COVID-19 infection in the elderly were identified in the studies selected in this review. Cardiovascular disease was the main one, accounting for 72.72%, followed by diabetes (72.72%), hypertension (63.63%), chronic kidney disease and obesity with 27.27%, dementia and chronic obstructive pulmonary disease with 22.72%, cancer (18.18%), liver disease (9.09%), asthma, dyslipidemia, and depression with 4.54%. Final Considerations: It can be concluded that the main comorbidities observed in the health of the elderly in the face of the COVID-19 pandemic are associated with a significant increase in the risk of hospitalization and a high mortality rate in this population. The real reason why SARS-CoV-2 infections are more severe and fatal in the elderly is not yet well elucidated, viable hypotheses are emerging and encompass more than comorbidities, including immune repertoire, inflammasome activity, genetic and epigenetic influences.